IMPROVING THE PROFESSIONAL COMPETENCE OF PRIMARY SCHOOL STUDENTS FOR EDUCATIONAL ACTIVITIES (American Journal of Interdisciplinary Research and Development, 2022)
In accordance with the priorities set out in the Action Strategy for the further development of the Republic of Uzbekistan, the personal development of future teachers of professional education in higher education institutions was considered a topical issue. In increasing the spiritual needs of the student's personality, it is important to take into account the psychological requirements that require attention to his inner world, which has a special logic of development. Therefore, their ability to self-develop is ensured by the fact that they are equipped with development tools, the ability to possess it rationally, and their systematic use.